TiO2 / BN hydrosol with high solid content and high catalytic efficiency as well as preparation method and application of TiO2 / BN hydrosol

By combining the mechanical ball milling method and the liquid phase exfoliation method, a high solid content TiO2/BN hydrosol was prepared, which solved the problem of insufficient dispersion of BN hydrosol in the existing technology and significantly improved the efficiency and stability of the photocatalytic reaction.

CN119346155AActive Publication Date: 2025-01-24QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411641482.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-24
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing BN peeling technology is difficult to obtain BN hydrosols with high solids content and excellent dispersion, resulting in poor performance of TiO2/BN composite materials in photocatalytic reactions.

Method used

Using a method that combines mechanical ball milling and liquid phase exfoliation, BN is efficiently exfoliated to prepare high solid content TiO2/BN hydrosol. This method generates BN slurry through ball milling, and then improves the dispersion and stability of BN through liquid phase exfoliation and addition of polymer.

Benefits of technology

It significantly improves the solid content and decentralized performance of TiO2/BN water solution, enhances its absorption capacity within the visible light range and the separation efficiency of the pair of photochemical-grounded acupoints, and significantly improves the activity and stability of the photocatalytic reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005138578080000011
    Figure HDA0005138578080000011
  • Figure HDA0005138578080000012
    Figure HDA0005138578080000012
  • Figure HDA0005138578080000021
    Figure HDA0005138578080000021
Patent Text Reader

Abstract

According to the TiO2 / BN hydrosol with the high solid content and the high catalytic efficiency and the preparation method thereof, a mechanical ball milling method and a liquid phase stripping method are combined, the high-solid-content TiO2 / BN hydrosol is prepared in batches in a simple and low-cost mode, the obtained TiO2 / BN hydrosol is high in yield, good in stability and easy to store, a needed solvent is cheap, and the preparation method is simple, practical and suitable for industrial production. The advantages of a mechanical ball milling method and a liquid phase stripping method are fully fused, raw materials are cheap and easy to obtain, large-scale industrial production is facilitated, and remarkable economic and social benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a TiO2 / BN hydrosol with high solid content and high catalytic efficiency and a preparation method and application thereof, belonging to the technical field of material preparation and photocatalysis. Background Art

[0002] In recent years, with the acceleration of industrialization, the widespread use of colored dyes has made their harm to the environment and human health increasingly prominent. These dyes can release a variety of toxic and harmful substances during production and use, leading to water pollution and deterioration of air quality. Photocatalytic technology, as an emerging environmental governance method, shows good prospects. Photocatalysts can effectively degrade colored dyes under light conditions and convert them into harmless substances.

[0003] Titanium dioxide (TiO2) is one of the most efficient semiconductor photocatalysts with the characteristics of high photocatalytic activity, low cost and environmental friendliness. However, the practical application of titanium dioxide is limited by its inherent defects, such as limited light absorption range, easy recombination of electrons and holes, and insufficient surface active sites. In recent years, in order to improve the absorption of TiO2 to visible light, researchers have synthesized new TiO2-based composite materials by methods such as bismuth (Bi) doping and nitrogen (N) doping. These materials can effectively absorb visible light due to their low energy band gap and improve the efficiency of photocatalytic reactions (Li et al., 2020). Constructing a heterojunction between TiO2 and other semiconductors can effectively inhibit the recombination of electrons and holes and improve the quantum yield. For example, the heterojunction formed by TiO2 and gallium nitride (GaN) shows better photocatalytic performance and stability (Zhang et al., 2021). In addition, through surface modification techniques, such as metal / non-metal loading and the introduction of nanostructures, researchers have increased the surface active sites of TiO2, improved the adsorption capacity of reactants, and significantly enhanced the catalytic activity of TiO2 in the degradation of organic pollutants (Chen et al., 2023).

[0004] Boron nitride (BN) is a ceramic material that is resistant to high temperatures, wear and corrosion, and has good thermal conductivity. It is widely used in high-temperature engineering, electronics, aerospace and other fields. Due to its two-dimensional sheet structure, high specific surface area and good adsorption capacity, it is often used as a catalyst carrier, but it does not respond to visible light. TiO2 and BN are compounded to form an interface, and electrons are transferred from TiO2 to BN through the interface, and the rapid separation of photogenerated electron-hole pairs is achieved by constructing a built-in electric field. However, since ordinary BN particles are too large, the surface is easy to adsorb oxygen and moisture, its surface activity is reduced, and the interaction force between it and the solvent is reduced, resulting in poor dispersion in the solvent. Therefore, directly mixing boron nitride with TiO2 cannot improve the photocatalytic performance.

[0005] In recent years, the stripping methods of BN mainly include mechanical stripping, chemical stripping, liquid phase stripping and other methods. Mechanical stripping usually uses physical means such as tape stripping to obtain a single layer or a few layers of BN; chemical stripping uses chemical solvents to reduce the interlayer bonding force to achieve stripping; liquid phase stripping disperses BN powder in a liquid, combined with ultrasonic treatment or high-speed stirring to promote interlayer separation to form a BN hydrosol. Mechanical stripping has low efficiency and it is difficult to accurately control the number of stripped layers, and it may cause damage to the material; chemical functionalization stripping requires attention to the standardized operation when using chemicals and requires waste treatment; liquid phase stripping faces problems such as insufficient dispersibility, solvent selection and high cost. Therefore, the existing stripping technology faces severe challenges in obtaining BN hydrosols with high solid content and excellent dispersibility. It is urgent to develop an efficient and controllable BN stripping method to enhance the solid content and dispersion properties of BN hydrosols and improve the catalytic performance of photocatalysts.

[0006] In summary, it is urgent to develop a new type of TiO2 / BN composite photocatalyst, which can enhance the visible light absorption of TiO2 and the separation efficiency of photogenerated electron-hole pairs by optimizing the stripping technology of BN and improving its dispersibility in the aqueous phase. This composite material is expected to significantly improve the activity and stability of the photocatalytic reaction, making it perform better in applications such as the degradation of organic pollutants. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a TiO2 / BN hydrosol with high solid content and high catalytic efficiency, and a preparation method and application thereof.

[0008] The present invention combines mechanical ball milling and liquid phase stripping to prepare TiO2 / BN aqueous sol with high solid content in a simple, low-cost and batch manner. The obtained TiO2 / BN aqueous sol has high yield, good stability, easy preservation, and cheap solvent. The preparation method is simple and practical, fully integrating the advantages of mechanical ball milling and liquid phase stripping. The raw materials are cheap and easy to obtain, which is conducive to large-scale industrial production and has significant economic and social benefits.

[0009] The present invention is achieved through the following technical solutions:

[0010] A method for preparing a TiO2 / BN hydrosol with high solid content and high catalytic efficiency comprises the following steps:

[0011] (1) Adding BN powder to a ball mill, adding anhydrous ethanol as a buffer, and ball milling for 10-12 hours to obtain BN slurry, drying the BN slurry, grinding it thoroughly, and sieving it to obtain preliminary BN powder;

[0012] (2) adding the preliminary BN powder into a mixed solution of deionized water and ethanol, stirring to make it evenly dispersed, and ultrasonically treating to obtain a high solid content BN suspension;

[0013] (3) Centrifuging the BN suspension and collecting the BN supernatant;

[0014] (4) mixing TiO2 nanopowder with BN supernatant and stirring to obtain a uniform and transparent TiO2 / BN solution;

[0015] (5) Slowly add polyvinyl pyrrolidone (PVP) or polyethylene glycol (PEG) to the TiO2 / BN solution and stir for 6-8 hours to obtain a TiO2 / BN hydrosol.

[0016] Preferably, according to the present invention, in step (1), the mass volume ratio of BN powder to anhydrous ethanol is (1-5):(10-50), in units of g / mL.

[0017] Preferably, in step (1), the ball milling is performed using steel balls with a diameter of 3-6 mm, the ball milling speed is 200-400 rpm, and the ball milling operation procedure is: working for 20-40 min and resting for 8-12 min.

[0018] Preferably, according to the present invention, in step (1), drying is performed at 50-70° C. for 6-10 h, and sieving is performed through a 60-mesh sieve.

[0019] Preferably, according to the present invention, in step (2), the mass volume ratio of BN powder to mixed solution is (0.01-0.3):(10-300), in units of g / mL.

[0020] Preferably, according to the present invention, in step (2), the volume ratio of deionized water to anhydrous ethanol in the mixed solution of deionized water and ethanol is 1:1.

[0021] Preferably according to the present invention, in step (2), the ultrasonic treatment is performed at 50-200W for 0.5-2h.

[0022] Preferably according to the present invention, in step (3), the centrifugation is performed at 7000-9000 rpm for 4-10 min.

[0023] Preferably, according to the present invention, in step (4), the mass volume ratio of TiO2 nanopowder to BN supernatant is (0.05-1):(15-300), in units of g / mL.

[0024] Preferably, according to the present invention, in step (4), the mass ratio of TiO2 nanopowder to BN dissolved in the supernatant is (0.05-1):(0.0015-0.3).

[0025] Preferably according to the present invention, in step (5), PVP is K90 polyvinyl pyrrolidone.

[0026] Preferably according to the present invention, in step (5), the weight average molecular weight of PVP is 1.3 million.

[0027] Preferably according to the present invention, in step (5), the average molecular weight of PEG is 2000.

[0028] Preferably according to the present invention, in step (5), the mass volume ratio of PVP or PEG to TiO2 / BN solution is (0.05-0.2):(15-60), in units of g / mL.

[0029] Preferably, in step (5), PVP or PEG needs to be added slowly. If a large amount is added violently at one time, stratification, agglomeration and the like will occur. Therefore, PVP or PEG needs to be added slowly.

[0030] As a high molecular weight polymer, PVP or PEG has good solubility and compatibility, which can effectively increase the viscosity of TiO2 / BN solution, thereby improving its fluidity and application performance. At the same time, it can inhibit the precipitation and aggregation of BN and TiO2 particles, thereby maintaining the uniformity and suspension of the hydrosol. Therefore, the addition of PVP or PEG greatly improves the dispersibility of high solid content TiO2 / BN hydrosol.

[0031] A TiO2 / BN aqueous sol with high solid content and high catalytic efficiency is prepared by the method.

[0032] The above-mentioned TiO2 / BN hydrosol is used for catalytic degradation of rhodamine B aqueous solution (RhB) under ultraviolet-visible light, and the volume ratio of TiO2 / BN hydrosol to rhodamine B aqueous solution (RhB) is (5-20):(20-80).

[0033] Compared with the prior art, this application has the following beneficial effects:

[0034] 1. The present invention innovatively combines mechanical ball milling with liquid phase exfoliation to efficiently exfoliate boron nitride (BN) nanosheets. This effectively overcomes the limitations of traditional mechanical ball milling in terms of exfoliation efficiency and the shortcomings of liquid phase exfoliation in terms of dispersibility and production cost, significantly improving the controllability and repeatability of the preparation process. The process is simple and efficient, and is highly feasible for industrial production, laying the foundation for large-scale application.

[0035] 2. The TiO2 / BN hydrosol prepared by the present invention exhibits high solid content and excellent dispersion properties, making it have broad prospects in the preparation and application of various high-performance materials. Its stability and controllability make the application of BN nanosheets in the fields of composite materials, coatings and sensors more flexible, and can meet the performance requirements of high-end industries for materials.

[0036] 3. The TiO2 / BN hydrosol of the present invention innovatively improves the absorption capacity of TiO2 in the visible light range through specific technical means, successfully solves the problems of high electron-hole recombination rate and insufficient surface active sites, and significantly enhances the efficiency of photodegradation reaction. This synergistic effect makes TiO2 / BN composite materials show great application potential in the field of photocatalysis, solving the problem that directly mixing boron nitride with TiO2 cannot improve the photocatalytic performance.

[0037] 4. The experimental results show that the degradation efficiency of the TiO2 / BN hydrosol of the present invention for rhodamine B (RhB) is as high as 99.41% within 30 minutes, which fully demonstrates its excellent performance in photocatalytic reactions. By optimizing the light absorption characteristics of TiO2 and the enhancement effect of BN nanosheets, it not only effectively promotes the separation of electrons and holes and improves the catalytic activity, but also improves the stability and durability of the photocatalyst. The experimental results not only clearly demonstrate the great potential of TiO2 / BN hydrosol in removing environmental pollutants, but also provide new scientific research ideas and directions for the development of efficient photocatalytic materials in the future, indicating its practical application prospects in the field of environmental governance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 : is a bar graph of particle size distribution of different BN hydrosols, a is the BN hydrosol prepared in step (4) of Example 1, and b is the BN hydrosol prepared in Comparative Example 4;

[0039] Figure 2 It is a bar chart comparing the solid contents of different BN hydrosols.

[0040] Figure 3 XRD spectra of the TiO2 / BN aqueous sol prepared in Example 1, the BN aqueous sol prepared in Comparative Example 1, and the TiO2 aqueous sol prepared in Comparative Example 2.

[0041] Figure 4 These are SEM images of the TiO2 / BN aqueous sol prepared in Example 1, (a) is the SEM image of the TiO2 / BN aqueous sol magnified 20,000 times, and (b) is the SEM image of the TiO2 / BN aqueous sol magnified 50,000 times.

[0042] Figure 5 (a) is the SEM image of the TiO2 / BN aqueous sol prepared in Example 1, (b) is the EDS spectrum of the TiO2 / BN aqueous sol prepared in Example 1, and (c) and (d) are element mapping diagrams of the TiO2 / BN aqueous sol prepared in Example 1.

[0043] Figure 6(a) is the TEM image of the BN aqueous sol prepared in Comparative Example 1, and (b) is the TEM image of the TiO2 / BN aqueous sol prepared in Example 1.

[0044] Figure 7 HRTEM image of TiO2 / BN aqueous sol prepared in Example 1

[0045] Figure 8 The diffuse reflection absorption spectra of the TiO2 / BN aqueous sol prepared in Example 1, the BN aqueous sol prepared in Comparative Example 1, and the TiO2 aqueous sol prepared in Comparative Example 2 are shown.

[0046] Fig. 9 The photocurrent curves of the TiO2 / BN aqueous sol prepared in Examples 1-3, the BN aqueous sol prepared in Comparative Example 1, and the TiO2 aqueous sol prepared in Comparative Example 2 are shown.

[0047] Fig.10 Impedance curves of the TiO2 / BN aqueous sols prepared in Examples 1-3, the BN aqueous sol prepared in Comparative Example 1, and the TiO2 aqueous sol prepared in Comparative Example 2.

[0048] Fig.11 (a) is the RhB degradation graph of the TiO2 / BN hydrosols prepared in Examples 1-5, the BN hydrosols prepared in Comparative Example 1, and the TiO2 hydrosols prepared in Comparative Example 2; (b) is the RhB degradation graph of the TiO2 / BN hydrosols prepared in Example 6 and Comparative Examples 6-10. DETAILED DESCRIPTION

[0049] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, the embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0050] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified; and the equipment used are conventional equipment.

[0051] Example 1

[0052] The preparation method of TiO2 / BN hydrosol with high solid content and high catalytic efficiency comprises the following steps:

[0053] (1) Add 3 g of BN powder into a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer, set the speed to 300 rpm, and ball mill for 12 h;

[0054] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0055] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0056] (4) The highly dispersed and high solid content BN suspension was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected. 0.1 g of TiO2 nanopowder was added to 30 mL of BN supernatant and stirred for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume of about 30 mL).

[0057] (5) Weigh 0.1 g of PVP and slowly add it to the TiO2 / BN solution in step (4), and stir for 8 h to obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:30) aqueous sol.

[0058] Example 2

[0059] The preparation method of TiO2 / BN hydrosol with high solid content and high catalytic efficiency comprises the following steps:

[0060] (1) Add 3 g of BN powder into a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer, set the speed to 300 rpm, and ball mill for 12 h;

[0061] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0062] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0063] (4) The highly dispersed and high solid content BN suspension was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected. 0.05 g of TiO2 nanopowder was added to 30 mL of BN supernatant and stirred for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume of about 30 mL).

[0064] (5) Weigh 0.1 g of PVP and slowly add it to the TiO2 / BN solution in step (4), stir for 8 h, and obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:15) aqueous sol.

[0065] Example 3

[0066] The preparation method of TiO2 / BN hydrosol with high solid content and high catalytic efficiency comprises the following steps:

[0067] (1) Add 3 g of BN powder into a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer, set the speed to 300 rpm, and ball mill for 12 h;

[0068] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0069] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0070] (4) The highly dispersed and high solid content BN suspension was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected. 0.2 g of TiO2 nanopowder was added to 30 mL of BN supernatant and stirred for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume of about 30 mL).

[0071] (5) Weigh 0.1 g of PVP and slowly add it to the TiO2 / BN solution in step (4), stir for 8 h, and obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:60) aqueous sol.

[0072] Example 4

[0073] The preparation method of TiO2 / BN hydrosol with high solid content and high catalytic efficiency comprises the following steps:

[0074] (1) Add 3 g of BN powder into a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer, set the speed to 300 rpm, and ball mill for 12 h;

[0075] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0076] (3) 30 mg of the obtained BN powder was added to 30 mL of a mixed solution of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to uniformly disperse the powder to obtain a BN suspension;

[0077] (4) The highly dispersed and high solid content BN suspension was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected. 0.1 g of TiO2 nanopowder was added to 30 mL of BN supernatant and stirred for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume of about 30 mL).

[0078] (5) Weigh 0.1 g of PVP and slowly add it to the TiO2 / BN solution in step (4), stir for 8 h, and obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:30) aqueous sol.

[0079] Example 5

[0080] The preparation method of TiO2 / BN hydrosol with high solid content and high catalytic efficiency comprises the following steps:

[0081] (1) Add 3 g of BN powder into a 50 mL ball mill, then add 40 mL of anhydrous ethanol as a buffer, set the speed to 300 rpm, and ball mill for 12 h;

[0082] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0083] (3) 30 mg of the obtained BN powder was added to a mixed solution of 20 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to uniformly disperse the powder to obtain a BN suspension;

[0084] (4) The highly dispersed and high solid content BN suspension was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected. 0.1 g of TiO2 nanopowder was added to 30 mL of BN supernatant and stirred for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume of about 30 mL).

[0085] (5) Weigh 0.1 g of PVP and slowly add it to the TiO2 / BN solution in step (2), stir for 8 h, and obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:30) aqueous sol.

[0086] Example 6

[0087] The preparation method of TiO2 / BN hydrosol with high solid content and high catalytic efficiency comprises the following steps:

[0088] (1) Add 3 g of BN powder to a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer. Set the speed to 300 rpm and ball mill for 12 h.

[0089] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0090] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0091] (4) The highly dispersed and high solid content BN suspension was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected. 0.1 g of TiO2 nanopowder was added to 30 mL of BN supernatant and stirred for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume of about 30 mL).

[0092] (5) Weigh 0.1 g of PEG and slowly add it to the TiO2 / BN solution in step (4), and stir for 8 h to obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:30) hydrosol.

[0093] Comparative Example 1

[0094] (1) Add 3 g of BN powder to a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer. Set the speed to 300 rpm and ball mill for 12 h.

[0095] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0096] (3) 30 mg of the obtained BN powder was added to 30 mL of a mixed solution of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then 100 W ultrasonic treatment was performed for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0097] (4) The dispersion was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected.

[0098] (5) Weigh 0.1 g of PVP and slowly add it to the BN supernatant in step (4), and stir for 8 h to obtain a BN hydrosol.

[0099] Comparative Example 2

[0100] (1) 0.1 g of TiO2 nanopowder was added to a 30 mL mixed solution of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and stirred for 30 min to obtain a uniform and transparent TiO2 solution (volume of about 30 mL);

[0101] (2) Weigh 0.1 g of PVP and slowly add it to the TiO2 solution in step (1), and stir for 8 h to obtain a TiO2 hydrosol.

[0102] Comparative Example 3

[0103] (1) Add 3 g of BN powder into a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer, set the speed to 300 rpm, and ball mill for 12 h;

[0104] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0105] (3) 30 mg of the obtained BN powder was added to 30 mL of a mixed solution of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it uniformly dispersed. The dispersion was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected to obtain a BN hydrosol.

[0106] Comparative Example 4

[0107] 30 mg of BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1). A magnetic stirrer was used to maintain a rotation speed of 500 rpm and stirred for 30 min to make it evenly dispersed. Then, it was assisted by 100 W ultrasonic treatment for 1 h. The dispersion was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected to obtain the ultrasonically treated BN hydrosol.

[0108] Comparative Example 5

[0109] 30 mg of BN powder was added to 30 mL of a mixed solution of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1). A magnetic stirrer was used to stir at a speed of 500 rpm for 30 min to make it evenly dispersed. The dispersion was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected to obtain a BN hydrosol.

[0110] Comparative Example 6

[0111] (1) Add 3 g of BN powder to a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer. Set the speed to 300 rpm and ball mill for 12 h.

[0112] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder.

[0113] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0114] (4) The dispersion was transferred to a test tube and centrifuged at 8000 rpm for 5 min. Then, the BN supernatant was carefully collected. 0.1 g of TiO2 nanopowder was added to 30 mL of BN supernatant and stirred for 30 min to obtain a uniform and transparent TiO2 / BN (TiO2 / BN molar ratio was 1:30) hydrosol.

[0115] Comparative Example 7

[0116] (1) Add 3 g of BN powder to a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer. Set the speed to 300 rpm and ball mill for 12 h.

[0117] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0118] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0119] (4) Transfer the dispersion to a test tube and centrifuge at 8000 rpm for 5 min. Then, carefully collect the BN supernatant. Add 0.1 g of TiO2 nanopowder to 30 mL of BN supernatant and stir for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume is about 30 mL);

[0120] (5) Weigh 0.01 g of PVP and slowly add it to the TiO2 / BN solution in step (4), and stir for 8 h to obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:30) aqueous sol.

[0121] Comparative Example 8

[0122] (1) Add 3 g of BN powder to a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer. Set the speed to 300 rpm and ball mill for 12 h.

[0123] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0124] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0125] (4) Transfer the dispersion to a test tube and centrifuge at 8000 rpm for 5 min. Then, carefully collect the BN supernatant. Add 0.1 g of TiO2 nanopowder to 30 mL of BN supernatant and stir for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume is about 30 mL);

[0126] (5) Weigh 0.01 g of PEG and slowly add it to the TiO2 / BN solution in step (4), and stir for 8 h to obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:30) hydrosol.

[0127] Comparative Example 9

[0128] (1) Add 3 g of BN powder to a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer. Set the speed to 300 rpm and ball mill for 12 h.

[0129] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0130] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0131] (4) Transfer the dispersion to a test tube and centrifuge at 8000 rpm for 5 min. Then, carefully collect the BN supernatant. Add 0.1 g of TiO2 nanopowder to 30 mL of BN supernatant and stir for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume is about 30 mL);

[0132] (5) Weigh 0.3 g of PVP and slowly add it to the TiO2 / BN solution in step (4), and stir for 8 h to obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:30) aqueous sol.

[0133] Comparative Example 10

[0134] (1) Add 3 g of BN powder to a 50 mL ball mill, then add 30 mL of anhydrous ethanol as a buffer. Set the speed to 300 rpm and ball mill for 12 h.

[0135] (2) The ball-milled BN slurry was placed in an oven at 60°C and dried for 8 h. The resulting BN white powder was fully ground and sieved with a 60-mesh sieve to obtain a preliminary BN powder;

[0136] (3) 30 mg of the obtained BN powder was added to a mixed solution of 30 mL of deionized water and ethanol (the volume ratio of deionized water to anhydrous ethanol was 1:1), and a magnetic stirrer was used to stir for 30 min at a speed of 500 rpm to make it evenly dispersed, and then ultrasonically treated at 100 W for 1 h to obtain a BN suspension with high dispersion and high solid content;

[0137] (4) Transfer the dispersion to a test tube and centrifuge at 8000 rpm for 5 min. Then, carefully collect the BN supernatant. Add 0.1 g of TiO2 nanopowder to 30 mL of BN supernatant and stir for 30 min to obtain a uniform and transparent TiO2 / BN solution (volume is about 30 mL);

[0138] (5) Weigh 0.3 g of PEG and slowly add it to the TiO2 / BN solution in step (4), and stir for 8 h to obtain a TiO2 / BN (TiO2 / BN molar ratio is 1:30) hydrosol.

[0139] Experimental example

[0140] The following analysis experiments were performed on the materials of Examples 1-6 and Comparative Examples 1-10:

[0141] 1. Particle size analysis: Figure 1 (a) is a particle size distribution bar graph of the BN hydrosol obtained in Comparative Example 4, and (b) is a particle size distribution bar graph of the BN hydrosol in step (4) of Example 1. Figure 1 It can be seen from (a) that the particle size distribution of BN particles without ball milling and ultrasonic treatment is relatively dispersed (0.05-45μm), 39.28% of the BN particles have a particle size distribution of 2-5μm, and 15.14% of the BN particles have a particle size of more than 10μm. Figure 1 (b) shows that the particle size distribution of the BN particles in the BN hydrosol prepared in Example 1 is concentrated in the range of 0.5-2 μm, and 84.2% of the BN particles are distributed in the range of 0.8-1.5 μm. The particle size distribution bar chart shows that the particle size of the BN particles is significantly reduced after being treated by ball milling ultrasound, which indicates that the treatment method effectively breaks up the particles and increases their specific surface area, thereby improving their reactivity and efficiency in applications such as catalysis and adsorption. In addition, the reduction in particle size also helps to improve the dispersibility and uniformity of the material.

[0142] 2. Solid content test: Prepare four centrifuge tubes, weigh and record the weight of the centrifuge tubes, transfer the BN hydrosol in step (4) of Example 1 and the BN hydrosol prepared in Comparative Examples 3-5 into centrifuge tubes of known mass, place them in a vacuum drying oven at 60°C, and vacuum dry them for 12 hours. Then weigh and record the mass of the centrifuge tubes after vacuum drying, and calculate the mass of the centrifuge tubes according to the formula: The solid content of BN hydrosol is obtained as Figure 2 As shown. Where G is the solid content of the hydrosol, in mg / ml; m1 is the mass of the centrifuge tube, m2 is the mass of the centrifuge tube after vacuum drying, in g; v is the volume of the hydrosol, in mL.

[0143] from Figure 2 It can be seen that the BN hydrosol in Example 5 without any treatment has the smallest solid content of 0.063 mg / mL, and the BN hydrosol treated with ball milling ultrasound in Example 1 has the largest solid content of 0.107 mg / mL. The solid content of the BN hydrosol increased by 70% after ball milling ultrasound treatment. Further analysis shows that the ball milling ultrasound treatment significantly improves the dispersibility and stability of the BN hydrosol. This may be related to the reduction in the size of the BN particles and the increase in surface energy during the treatment process, which promotes its uniform distribution in the aqueous phase. In addition, the increase in solid content not only reflects the increase in the effective addition amount of BN, but also means its better dispersibility in the hydrosol, which helps to improve performance in subsequent applications.

[0144] 3. XRD test: Figure 3 XRD spectra of the TiO2 / BN aqueous sol prepared in Example 1, the BN aqueous sol prepared in Comparative Example 1, and the TiO2 aqueous sol prepared in Comparative Example 2. The XRD spectra show that the crystal structure of the TiO2 / BN aqueous sol is consistent with that of the TiO2 in Comparative Example 2, and the relevant diffraction peaks of BN can be detected, indicating that the TiO2 / BN aqueous sol is successfully prepared.

[0145] 4. SEM test and element mapping analysis: Use a dropper to absorb the TiO2 / BN aqueous sol prepared in Example 1, and drop 2-3 drops of TiO2 / BN aqueous sol on an area of ​​1 cm 2 The conductive glass was placed in an oven at 40°C and dried for 7 hours to obtain a membrane material. The dried conductive glass was adhered to the conductive adhesive with the side coated with TiO2 / BN hydrosol facing upward. After gold spraying, the membrane material was tested by SEM and EDS. Figure 4 The SEM images of the TiO2 / BN hydrosol prepared in Example 1 are shown in Figure 1. (a) is a SEM image of the TiO2 / BN hydrosol magnified 20,000 times, and (b) is a SEM image of the TiO2 / BN hydrosol magnified 50,000 times. Figure 4 It can be seen that the TiO2 nanoparticles are around 5nm, with a small particle size, and are evenly attached to the BN nanosheets, increasing the active sites for the photocatalytic reaction. Figure 5 a is a SEM image of the TiO2 / BN hydrosol prepared in Example 1, Figure 5 b is the EDS spectrum of the TiO2 / BN hydrosol prepared in Example 1, Figure 5 c. Figure 5d is the element mapping diagram of the TiO2 / BN aqueous sol prepared in Example 1. The EDS spectrum proves the existence of various elements in the sample, and the element mapping diagram further proves that various elements in the TiO2 / BN aqueous sol are uniformly distributed.

[0146] 5. TEM test: Figure 6 a is the TEM image of BN hydrosol prepared in Comparative Example 1, Figure 6 b is the TEM image of TiO2 / BN hydrosol obtained in Example 1. Figure 6 By comparison, it can be seen that the incorporation of TiO2 makes the originally smooth surface of the BN nanosheets become uneven, increasing the specific surface area of ​​the material and providing more active sites.

[0147] 6. HRTEM test: Figure 7 This is the HRTEM image of the TiO2 / BN aqueous sol prepared in Example 1. The interplanar spacing in the selected area is 0.171nm and 0.216nm, corresponding to the (105) crystal plane of TiO2 and the (100) crystal plane of BN, respectively. This indicates that the grain boundary interaction during the formation of the TiO2 / BN aqueous sol promotes the good combination of the two materials.

[0148] 7. UV-Vis DRS analysis: The diffuse reflection absorption spectra UV-Vis DRS analysis results of Example 1 and Comparative Examples 1-2 are as follows: Figure 8 As shown, the results show that the BN hydrosol and TiO2 hydrosol prepared in Comparative Examples 1-2 have light absorption only in the ultraviolet region, and no light absorption in the visible region. The TiO2 / BN hydrosol prepared in Example 1 has light absorption in both the ultraviolet and visible regions, which shows that the optical properties of the TiO2 / BN hydrosol give it significant advantages in light energy conversion and utilization. By introducing BN, the light absorption range of the hydrosol has been expanded, which can effectively capture more solar energy, thereby improving the efficiency of the photocatalytic reaction.

[0149] 8. Photocurrent analysis: The materials of Examples 1-3 and Comparative Examples 1-2 were subjected to photocurrent analysis. The results are as follows: Fig. 9 As shown in , the TiO2 / BN aqueous sol prepared in Example 1 has the strongest photocurrent response ability, which indicates that the TiO2 / BN aqueous sol can effectively generate more photogenerated electrons under light, exhibits excellent photocurrent response performance, can quickly and effectively convert light energy into electrical energy, and promote the reaction rate in the photocatalytic process, thereby improving the overall reaction efficiency.

[0150] 9. AC impedance analysis: The materials of Examples 1-3 and Comparative Examples 1-2 were subjected to impedance analysis. The results are as follows: Fig.10 As shown in , the size of the arc reflects the transmission ability of photocatalyst electrons. The smaller the radius, the easier it is for electrons to be transmitted. Fig.10It can be seen that the TiO2 / BN hydrosol prepared in Example 1 has the smallest impedance and the largest electron transfer capacity. Compared with the hydrosol prepared in Comparative Examples 1-2, the structure of the composite hydrosol can reduce the energy loss of electrons during the migration process and further optimize the kinetics of the photocatalytic reaction. This enhanced electron transfer capacity not only improves the reaction rate of the photocatalyst, but also helps to improve the stability and efficiency of the photocatalytic process.

[0151] Application experiment example 1:

[0152] Photocatalytic Degradation of Rhodamine B (RhB)

[0153] The hydrosols prepared in Examples 1-6 and Comparative Examples 1-2 and 6-10 were applied to the photocatalytic degradation of a Rhodamine B (RhB) solution, the concentration of which was 20 mg / L, and the specific steps were as follows:

[0154] Photocatalytic degradation method: At room temperature, 9 mL of the above different hydrosols were added to 36 mL of rhodamine B (RhB) solution, and magnetically stirred in a photochemical reactor for 30 min to achieve adsorption-desorption equilibrium; an 800 W xenon lamp light source was used to simulate reference sunlight, and the solution was taken every 5 min, and the absorbance was detected using a UV-2550 spectrophotometer. The results are shown in Table 1 and Fig.11 shown.

[0155] Table 1 Comparison of degradation rate and degradation time of photocatalytic degradation of RhB by different samples

[0156] Serial number sample Degradation rate Degradation time 1 Example 1 99.41% 30min 2 Example 2 90.03% 30min 3 Example 3 82.97% 30min 4 Example 4 98.48% 30min 5 Example 5 97.33% 30min 6 Example 6 98.65% 30min 7 Comparative Example 1 1.12% 30min 8 Comparative Example 2 3.9% 30min 9 Comparative Example 6 79.11% 30min 10 Comparative Example 7 96.1% 30min 11 Comparative Example 8 95.54% 30min 12 Comparative Example 9 86.5% 30min 13 Comparative Example 10 84.6% 30min

[0157] It can be seen from Table 1 that within the same degradation time, the degradation rate of the TiO2 / BN hydrosol RhB prepared in Example 1 is the largest, which is 99.41%, and the degradation rate of the BN hydrosol RhB prepared in Comparative Example 1 is the smallest, which is 1.12%.

[0158] Fig.11 (a) is the RhB degradation diagram of the TiO2 / BN hydrosol prepared in Examples 2-5, the BN hydrosol prepared in Comparative Example 1, and the TiO2 hydrosol prepared in Comparative Example 2. Fig.11 It can be seen from the degradation curve of (a) that the hydrosol prepared in Example 4-5 has a higher photocatalytic degradation rate, and its adsorption capacity and photocatalytic degradation capacity are both superior to those of the hydrosol prepared in Example 2-3, but the adsorption capacity and photocatalytic degradation capacity of Example 2-3 are both superior to those of Comparative Example 1-2, and the degradation efficiency of Comparative Example 1-2 is much lower than that of Example 2-5, which indicates that the introduction of BN has a significant promoting effect on the photocatalytic ability of TiO2. Fig.11 (b) is a RhB degradation diagram of TiO2 / BN hydrosols obtained in Example 1, Example 6 and Comparative Examples 6-10. Fig.11 It can be clearly observed in (b) that the TiO2 / BN hydrosol prepared in Example 1 exhibits the highest photocatalytic degradation rate, while the TiO2 / BN hydrosol in Comparative Example 6 exhibits the lowest degradation efficiency. At the same time, the photocatalytic degradation rates of the TiO2 / BN hydrosols prepared in Example 1 and Example 6 are similar, and the photocatalytic degradation rates of Comparative Example 7 and Comparative Example 8 also show similar performances, and the degradation rates between Comparative Example 9 and Comparative Example 10 are also close, but too much or too little PVP and PEG in Comparative Examples 7-10 will reduce the performance of the hydrosol. These results show that adding PVP or PEG to the TiO2 / BN hydrosol can significantly improve its photocatalytic degradation rate, and PVP and PEG have similar effects on the performance of the hydrosol. The appropriate addition of additives to the TiO2 / BN hydrosol can effectively prevent the agglomeration of particles, thereby increasing the specific surface area of ​​the catalyst, and thus improving the overall efficiency of the photocatalytic reaction.

Claims

1. A method for preparing a TiO2 / BN hydrosol with high solid content and high catalytic efficiency, comprising the following steps: (1) Adding BN powder to a ball mill, adding anhydrous ethanol as a buffer, and ball milling for 10-12 hours to obtain BN slurry, drying the BN slurry, grinding it thoroughly, and sieving it to obtain preliminary BN powder; (2) adding the preliminary BN powder into a mixed solution of deionized water and ethanol, stirring to make it evenly dispersed, and ultrasonically treating to obtain a high solid content BN suspension; (3) Centrifuging the BN suspension and collecting the BN supernatant; (4) mixing TiO2 nanopowder with BN supernatant and stirring to obtain a uniform and transparent TiO2 / BN solution; (5) Slowly add polyvinyl pyrrolidone (PVP) or polyethylene glycol (PEG) to the TiO2 / BN solution and stir for 6-8 hours to obtain a TiO2 / BN hydrosol.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass volume ratio of BN powder to anhydrous ethanol is (1-5):(10-50), in units of g / mL.

3. The preparation method according to claim 1, characterized in that: In step (1), the ball milling is carried out using steel balls with a diameter of 3-6 mm, the ball milling speed is 200-400 rpm, and the ball milling operation program is: working for 20-40 min, resting for 8-12 min, drying at 50-70° C. for 6-10 h, and sieving through a 60-mesh sieve.

4. The preparation method according to claim 1, characterized in that: In step (2), the mass volume ratio of BN powder to the mixed solution is (0.01-0.3):(10-300), unit: g / mL, the volume ratio of deionized water to anhydrous ethanol in the mixed solution of deionized water and ethanol is 1:1, and the ultrasonic treatment is performed at 50-200W for 0.5-2h.

5. The preparation method according to claim 1, characterized in that: In step (3), the centrifugation is performed at 7000-9000 rpm for 4-10 min.

6. The preparation method according to claim 1, characterized in that: In step (4), the mass volume ratio of TiO2 nanopowder to BN supernatant is (0.05-1):(15-300), unit: g / mL, and the mass ratio of TiO2 nanopowder to BN dissolved in the supernatant is (0.05-1):(0.0015-0.3).

7. The preparation method according to claim 1, characterized in that: In step (5), PVP is K90 polyvinyl pyrrolidone, the weight average molecular weight of PVP is 1.3 million, and the average molecular weight of PEG is 2000.

8. The preparation method according to claim 1, characterized in that: In step (5), the mass volume ratio of PVP or PEG to TiO2 / BN solution is (0.05-0.2):(15-60), unit: g / mL.

9. A TiO2 / BN hydrosol with high solid content and high catalytic efficiency, prepared by the method described in any one of claims 1 to 8.

10. Use of the TiO2 / BN hydrosol according to claim 9 for catalytic degradation of Rhodamine B aqueous solution (RhB) under ultraviolet-visible light, wherein the volume ratio of the TiO2 / BN hydrosol to the Rhodamine B aqueous solution (RhB) is (5-20):(20-80).

Citation Information

Patent Citations

  • Method for preparing BN (boron nitride) alkene dispersion solution by combination of ball milling and liquid-phase peeling

    CN103130236A

  • Titanium dioxide / boron nitride composite material and preparation method and application thereof

    CN108083329A

  • Photocatalytic self-cleaning metal hydroxide / TiO2 hydrosol with amphiphilic structure as well as preparation method and application of photocatalytic self-cleaning metal hydroxide / TiO2 hydrosol

    CN117380172A

  • How to input password on electronic devices to prevent password leakage

    KR102650238B1